Nephrin, a transmembrane protein, is involved in pancreatic beta-cell survival signaling. (15th January 2015) - Kapodistria, Katerina; Tsilibary, Effie-Photini; Politis, Panagiotis; Moustardas, Petros; Charonis, Aristidis; Kitsiou, Paraskevi
Highlights: We investigated the role of nephrin in mouse pancreatic βTC-6 cell survival. Nephrin–nephrin interactions triggered PI3-kinase-Akt survival signaling. Nephrin silencing inhibited nephrin-induced Akt activation and increased cell apoptosis. High glucose impaired nephrin-induced Akt signaling via nephrin internalization. Nephrin and pAkt levels were reduced in pancreatic islets of diabetic mice. Abstract: Nephrin, a cell surface signaling receptor, regulates podocyte function in health and disease. We study the role of nephrin in β-cell survival signaling. We report that in mouse islet β-cells and the mouse pancreatic beta-cell line (βTC-6 cells) nephrin is associated and partly co-localized with PI3-kinase. Incubation of cells with functional anti-nephrin antibodies induced nephrin clustering at the plasma membrane, nephrin phosphorylation and recruitment of PI3-kinase to nephrin thus resulting in increased PI3K-dependent Akt phosphorylation and augmented phosphorylation/inhibition of pro-apoptotic Bad and FoxO. Nephrin silencing abolished Akt activation and increased susceptibility of cells to apoptosis. High glucose impaired nephrin signaling, increased nephrin internalization and up-regulated PKCα expression. Interestingly, a marked decrease in nephrin expression and phosphorylated Akt was observed in pancreatic islets of db/db lepr−/− diabetic mice. Our findings revealed that nephrin is involved in β-cell survival and suggest that glucose-induced changes in nephrin signaling may contribute to gradual pancreatic β-cell loss in type 2 diabetes.